The Peptide-Encoding CLE25 Gene Modulates Drought Response in Cotton - Dayong Zhang; Qingfeng Zhu; Pu Qin; Lu Yu; Weixi Li; Hao Sun (Agriculture)
CLAVATA3 (CLV3)/endosperm surrounding region (CLE) peptides have been reportedly involved in plant growth and development, as well as responses to abiotic stresses. However, the stress resilience of most CLE genes in cotton remains largely unknown. Here, induced expression pattern analysis showed that GhCLE25 was obviously responsive to osmotic and salt treatments, indicating that GhCLE25 was involved in abiotic stress tolerance. Furthermore, silencing GhCLE25 or the exogenous application of CLE25p effectively led to reduced and enhanced drought tolerance, respectively, as indicated by the activities of the plants’ POD, SOD, CAT, and MDA contents, as well as their height and fresh weight. We found that the knockdown of GhCLE25 promoted seedling growth and development, with a higher plant height and fresh weight in GhCLE25-silenced plants in comparison to control plants. In addition, a comparative transcriptome analysis of TRV:00 versus TRV:GhCLE25 and Mock versus CLE25p revealed that the CLE25-mediated signaling pathway is mainly involved in defense response and phytohormone signaling. Collectively, these findings indicate diverse roles of CLE25 in regulating plant growth and response to environmental stimuli and highlight the potential utilization of CLE25 to improve drought stress in modern agriculture via CLE25p spraying.